About Black Amazonas in Cartagena of the Indies circa 1586-1587: an African Heritage - (:unkn) unknown (My University, 2020)
The great traveller Pedro Ordóñez de Ceballos, author of Viaje del mundo (1684), during a stay in Cartagena of Indias (Colombia), managed the repression against the maroon slaves of the surrounding of the city (1586-1587). He confronted a black amazon corps who makes think to these of the ancient kingdoms of Angola, Monomotapa or Dahomey. He had to fight with her leader, Polonia, whose warrior spirit and intelligence he admired, and ended by establish negotiations, among the first of New World in this matter.
Keywords: African Research